Determining Factors of Capital Structure Using the Trade Off Theory: A Case Study on the Indonesian Stock Exchange in the Period of 2016 - 2020 - Rosid, Mohammad Zainur; Hikmah, Khoirul; Herlianto, Didit (Universitas Mercu Buana, 2024)
This research is quantitative research which aims to cognize and analyze the determining factors of capital structure, namely profitability, asset structure, liquidity, sales growth and company size in issuers listed on the Indonesia Stock Exchange (BEI). This research is correlative research that uses secondary data from the Indonesian Stock Exchange. The sampling technique used is the purposive sampling method. The object of this research is issuers listed on the Indonesia Stock Exchange in the period 2016 to 2020, with the exception of issuers included in the financial sector. The analysis technique used in this research is linear regression using the IBM SPSS program. The results of this research are 1) Profitability has a significant negative effect on capital structure. 2) asset structure, liquidity and company size have no effect on capital structure, 3) sales growth has a significant positive effect on capital structure.